Plant Migration : The Dynamics of Geographic Patterning in Seed Plant Species - Sauer, Jonathan D. (Book collections on Project MUSE., 1988)
Using cases of plant migration documented by both historical and fossil evidence, Jonathan D. Sauer provides a landmark assessment of what is presently known, and not merely assumed, about the process.